Immunomodulatory Activity of Xestospongia sp. Ethanolic Extract Towards Interferon-gamma (IFN- Î³) and Tumor Necrosis Factor-alpha (TNF-Î±) Levels in Wistar Male Rats - Fristiohady, Adryan; Jumadil; Wahyuni; Malaka, Muh. Hajrul; Harnita, Wa Ode; Sadarun, Baru; Yodha, Agung Wibawa Mahatva; Saripuddin; Purnama, La Ode Muhammad Julian; Sahidin, Idin (Universitas Tadulako, 2020)
Xestospongia sp. is one of marine sponge belongs to demosponges class that mainly found in Southeast Sulawesi and the secondary metabolites contained in Xestospongia sp. suspected to have immunomodulatory activity. A previous study exhibited the immunomodulatory of Xestospongia sp. ethanolic extract (XEE) at dose of 300 and 400 mg/Kg BW by affecting the phagocytic activity of macrophages. Thus, this study aims to investigate the effect of XEE towards interferon-gamma (IFN-Î³) and tumor necrosis factor-alpha (TNF-Î±) at dose of 300 and 400 mg/Kg BW. Wistar male rats are divided into 4 groups (n=6) randomly and treated for 7 days orally each as follow: group I (XEE dose of 300 mg/KgBW); group II (XEE dose of 400 mg/KgBW); group III (0.5% NaCMC); and group IV (commercial phylantii extract). On day 8, animals were infected with Staphylococcus aureus and left for 1 hour. Animals were sacrificed and the blood was drawn by cardiac puncture (3 mL), followed by analyzed under ELISA Kit for IFN-Î³ and TNF-Î±. Collected data were analyzed statistically using SPSSÂ®. The IFN-Î³ levels obtained were 350.113; 392.970; 118.416; and 61.958 Ïg/mL, respectively and the TNF-Î± were 2808; 1308; 778; and 845.5 Ïg/mL, respectively. According to results obtained, both doses of XEE are affecting the IFN-Î³ and TNF-Î± levels (p<0.05) compared to group III as negative control, and group IV as positive control. As conclusion, XEE of both doses is increasing IFN-Î³ and TNF-Î± levels of animals that respond to phagocytic activity